The learning: from a holistic and integrative approach (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2016)
Learning in any form is a complex and systematic process, whose origin could be attributed to the need of every living organism to reach its equilibrium with the environment, in order to stay alive and achieve their goals. Therefore, in view of its complexity and importance within the educational context, specialists in the area of learning have tried to synergistically integrate different approaches or schools of thought that explain it, with the purpose of generating explanations and expanded definitions that supports the creation of new models of teaching and learning. This research has as main objective to present an epistemological support as a basis for the construction of a (proposed) expanded definition of learning, which could guide the development of new educational models focused on the consolidation of meaningful learning in educational settings. This through a holistic and integrative analysis of the various theories that revolve around learning, such as autopoiesis, behaviorism, constructivism, cognitivism, and the general systems theory, based on Maturana and Varela (2003), Ruiz (2008), Ormrod (2005), Piaget (2009), Rodríguez and Torres (2003), Johansen (2009) and others, with a non-experimental design a deductive rationalist approach, and the explanatory scope. To achieve this goal, the above theories were reviewed and analyzed, identifying isomorphisms and establishing associations with learning, proposing as a final product an expanded definition of this important process.
Keywords: learning; meaningful learning; isomorphisms; holistic analysis